Private support for public disaster aid - Thomas Husted; David B. Nickerson (Journal of Risk and Financial Management, 2021)
Despite its growing economic and political importance, this is the first study in economics to investigate public opinion in the United States regarding both the allocation of government disaster aid to stricken households and communities as well as total expenditures by government on such aid. This is also the first study to bridge a gap in previous research on disasters by comparing and contrasting our results to related behavioral studies from political science, social psychology and sociology. Combining individual data from the 2006 General Social Survey with county-level information about the local environment of survey respondents, we estimate probit models to ascertain the magnitude and significance of the socioeconomic, demographic, political and experiential determinants of public opinion on these issues. Among other results, we find that Black survey respondents strongly support increasing total aid expenditures and aid to affected households and communities while income, age and a conservative political ideology largely exert a negative influence on these same variables. Surprisingly, the effects of prior experience with disasters and educational level have only a weak effect on the allocation of aid and none on the level of expenditures on aid. These and other results are consistent with only a portion of previous findings from other disciplines. Several implications of our results for current federal disaster policy are discussed and we also suggest directions for further research into this important topic.
Keywords: 330; natural disasters; political economy; survey data and methods